2013
DOI: 10.1136/bmjqs-2012-001502
|View full text |Cite
|
Sign up to set email alerts
|

How can clinical practice guidelines be adapted to facilitate shared decision making? A qualitative key-informant study

Abstract: This study resulted in an overview of strategies to adapt clinical practice guidelines to facilitate shared decision making. Some strategies seemed more contentious than others. Future research should assess the feasibility and impact of these strategies to make clinical practice guidelines more conducive to facilitate shared decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 24 publications
(13 reference statements)
1
65
0
1
Order By: Relevance
“…This finding is worthy of further exploration, given that age is one of the strongest risk factors for CVD, as it runs counter to the concept of absolute CVD risk and proposals based solely on an age cut-off 34 35. We acknowledge that in clinical practice GPs may have various and valid reasons for deviating from the guidelines, and strict adherence to guidelines and/or treatment thresholds may undermine the shared decision-making (SDM) approach that is now considered gold standard 36 37. SDM in the current context would entail that a GP assesses absolute CVD risk, explains this and the recommended management approach to the patient, discusses the benefits and harms of the different management options with the patient, and makes a shared decision with the patient.…”
Section: Discussionmentioning
confidence: 98%
“…This finding is worthy of further exploration, given that age is one of the strongest risk factors for CVD, as it runs counter to the concept of absolute CVD risk and proposals based solely on an age cut-off 34 35. We acknowledge that in clinical practice GPs may have various and valid reasons for deviating from the guidelines, and strict adherence to guidelines and/or treatment thresholds may undermine the shared decision-making (SDM) approach that is now considered gold standard 36 37. SDM in the current context would entail that a GP assesses absolute CVD risk, explains this and the recommended management approach to the patient, discusses the benefits and harms of the different management options with the patient, and makes a shared decision with the patient.…”
Section: Discussionmentioning
confidence: 98%
“…The second type of personalization of care focuses on how guidelines are used in the clinic. Instead of gold standards to be followed by doctors, guidelines are reimagined as decision aids that provide (standardized) information on various options that doctors and their patients discuss, interpret, modify or ignore (Boivin et al, 2009;Van der Weijden et al, 2013). Guideline development organizations are producing additional tools such as patient versions and patient decisions aids to encourage the involvement of individual consumers to weighing their own options in clinical practice (Raats et al, 2008).…”
Section: Consumer Choice: Personalizing Standards and Carementioning
confidence: 99%
“…Treatment decisions require weighing (in)comparable risks and benefits, for example, two treatments with similar outcomes (Greer et al, 2002;Van der Weijden et al, 2013). Instead of relying on guideline developers' impressions of patients preferences, methods are sought that provide evidence of patients' preferences: surveys of large patient populations; qualitative research (focus groups, interviews); or literature searches to locate existing research that has identified preferences (Chong et al, 2009;Diaz del Campo et al, 2011).…”
Section: Consumer Choice: Personalizing Standards and Carementioning
confidence: 99%
“…These concerns suggest the importance of looking at the problem of decision making from a strategic point of view, given that most operations require an integrated approach both at the higher levels as well as the operational level [35]. Van der Weijden et al [36] even conducted a qualitative keyinformant study with group discussions and semi-structured interviews to explore how clinical decision processes can be constructed to facilitate shared decision making. All these approaches were developed with the purpose of providing strategies to make clinical practice guidelines more reliable and representative to facilitate shared decision making.…”
Section: Performance Assessment Model For Hospital Management Purposesmentioning
confidence: 98%